Awareness Level on Fast Food Selection Factors Among Catering Students - Zakariah, Siti Hajar binti Zakariah; Abd Razak, Nur Farhana; Ismail, Lisa Mariam Syawal; Tukiran, Nor Anis Intan Aqiah; Ahmad, Nor Aziah (Online Journal for TVET Practitioners, 2023)
Consumption of fast food among students regularly or uncontrolled can contribute to various long-term health problems in the future. This is because, fast food contains ingredients that can leave an impact on a person’s health in the short term and also in the long-term if its intake is uncontrolled. There are various factors that influence these students in the selection of fast food. Therefore, this study was conducted to find out the awareness of fast food intake among catering students and the relationship with fast food selection. This study was conducted based on a quantitative descriptive survey method using a questionnaire instrument and were analyzed descriptively and inferentially. The data obtained were analyzed using Statistical Package for the Social Sciences (SPSS) version 26 to obtain the mean values, standard deviation and Spearman Rank to see the relationship. Overall, this study shows that the main factors of fast food selection among catering students are service factors and purchases incentives with means score of 4.29. While the level of awareness of students on the long-term effects of fast food intake is high with mean scores 4.08. The results of this study are expected to help students to practice healthier food choices to prevent any long -term diseases and have a healthy survival in the future.